Urban evolution comes into its own: Emerging themes and future directions of a burgeoning field. (7th December 2020) - Miles, Lindsay S.; Carlen, Elizabeth J.; Winchell, Kristin M.; Johnson, Marc T. J.
Abstract: Urbanization has recently emerged as an exciting new direction for evolutionary research founded on our growing understanding of rapid evolution paired with the expansion of novel urban habitats. Urbanization can influence adaptive and nonadaptive evolution in urban‐dwelling species, but generalized patterns and the predictability of urban evolutionary responses within populations remain unclear. This editorial introduces the special feature "Evolution in Urban Environments" and addresses four major emerging themes, which include: (a) adaptive evolution and phenotypic plasticity via physiological responses to urban climate, (b) adaptive evolution via phenotype–environment relationships in urban habitats, (c) population connectivity and genetic drift in urban landscapes, and (d) human–wildlife interactions in urban spaces. Here, we present the 16 articles (12 empirical, 3 review, 1 capstone) within this issue and how they represent each of these four emerging themes in urban evolutionary biology. Finally, we discuss how these articles address previous questions and have now raised new ones, highlighting important new directions for the field.